Driving consequences of sleepiness in Canadians with obstructive sleep apnea: A population survey. Issue 5 (14th November 2022) - Povitz, M.; Bansback, N.; Fenton, M.; Almeida, F.; Ratycz, D.; Huynh, N.; Ayas, N.T.; Chiu, J.A.; Pendharkar, S.R.
Abstract: INTRODUCTION: Untreated OSA has been associated with an increased risk of motor vehicle crashes. Previous studies are now 2 decades old and may have been impacted by bias; thus, modern, anonymous estimates are needed. MATERIALS AND METHODS: We conducted an anonymous survey, which asked about experiences with OSA, including the impact of OSA on driving. Logistic regression models were used to assess the association between the risk of falling asleep while driving and crashes/near miss and potential predictors, including OSA severity, age, sex, hours driven per week, current treatment and work schedule. RESULTS: Six hundred complete responses were received. Ninety percent of respondents drove regularly with 72% driving between 1 and 20 hours a week. Twenty-eight percent of respondents reported having fallen asleep while driving and 5% had experienced a crash or near miss related to sleepiness within the previous 5 years. After adjusting for OSA severity, age, sex and hours driven per week, falling asleep while driving was associated with severe OSA (OR 1.76 [95% CI 1.05, 3.01]) and higher age (in years) (OR 0.98 [95% CI 0.97, 1.00]). Use of continuous positive airway pressure (CPAP) and higher age were associated with reduced crash or near miss in the multivariable analysis (OR 0.27 [95% CI 0.08, 0.89]; OR 0.96 [95% CI 0.92, 1.00]), and shift work was associated with increased risk (OR 3.26 [95% CI 1.08, 10.11]). CONCLUSIONS: Falling asleep or crashing while driving remains common among individuals with OSA. This supports continued efforts to identify and treat affected individuals. RÉSUMÉ: INTRODUCTION: L'apnée obstructive du sommeil (AOS) non traitée a été associée à un risque accru d'accidents de la route. Les études antérieures datent maintenant de deux décennies et peuvent avoir été influencées par des biais; par conséquent, des estimations modernes et anonymes sont nécessaires. MATÉRIELS ET MÉTHODES: Nous avons mené une enquête anonyme, qui posait des questions sur les expériences avec l'AOS y compris ses répercussions sur la conduite. Des modèles de régression logistique ont été utilisés pour évaluer l'association entre le risque de s'endormir en conduisant et les accidents/quasi-accidents de même que les prédicteurs potentiels, y compris la gravité de l'AOS, l'âge, le sexe, le nombre d'heures de conduite par semaine, le traitement actuel et l'horaire de travail. RÉSULTATS: Six cents réponses complètes ont été reçues. Quatre-vingt-dix pour cent des répondants conduisaient régulièrement et 72 % conduisaient entre 1 et 20 heures par semaine. Vingt-huit pour cent des répondants ont déclaré s'être endormis en conduisant et 5 % avaient eu un accident ou un quasi-incident lié à la somnolence au cours des cinq années précédentes. Après ajustement en fonction de la gravité de l'AOS, de l'âge, du sexe et du nombre d'heures de conduite par semaine, l'endormissement pendant la conduite était associé à une AOS sévère (RC 1, 76 [IC à 95 % 1, 05, 3, 01]) et à un âge plus élevé (en années) (RC 0, 98 [IC à 95 % 0, 97, 1, 00]). Dans l'analyse multivariable, l'utilisation d'un appareil CPAP et un âge plus élevé étaient associés à une réduction du nombre d'accidents ou d'accidents évités de justesse (RC 0, 27 [IC à 95 % 0, 08, 0, 89]; RC 0, 96 [IC à 95 % 0, 92, 1, 00]), et le travail par quarts était associé à une augmentation du risque (RC 3, 26 [IC à 95 % 1, 08, 10, 11]). CONCLUSIONS: S'endormir ou avoir un accident en conduisant reste courant chez les personnes atteintes d'AOS. Ces conclusions vont dans le sens de la poursuite des efforts visant à repérer et à traiter les personnes touchées.